Dynamics and landscape of academic discourse on environmental attitudes and behaviors since the 1970s - Telesiene, Audrone; Hadler, Markus (Frontiers in Sociology, 2023)
A wealth of knowledge about environmental attitudes and behaviors has been published and communicated via academic journals, yet there is a lack of effort to review and analyze this academic discourse systematically. This article aims to investigate the order and content of this discourse, i.e., which theoretical approaches have been employed and which empirical evidence was used to study individual environmental attitudes and behaviors. Based on initial research on Web of Science and SCOPUS and a detailed analysis of 200 papers on environmental attitudes and behavior from the journal Environment and Behavior, this paper combines systematic literature review and quantitative content analysis methods to explore the characteristics of an academic discourse that started in the 1970s. The results show the historical stages of the academic field, a growth of theoretical diversity and intensity of the academic discourse in the post-2000 period, a dominance of socio-psychological explanatory models, and a geographically limited empirical evidence base. The paper discusses the academic discourse's shortcomings and provides guidelines for further research.